Development of an upper-limb neuroprosthesis to voluntarily control elbow and hand. (18th August 2018) - Ogiri, Yosuke; Yamanoi, Yusuke; Nishino, Wataru; Kato, Ryu; Takagi, Takehiko; Yokoi, Hiroshi
ABSTRACT: This work reports on the research and development of a lightweight neuroprosthesis that can control impaired motion using voluntary biological signals. The total weight of the developed neuroprosthesis is 900 g, which is the weight of 40% of the defective limb. Further, it is lighter than commercially available models. For a transhumeral amputee who had targeted muscle reinnervation (TMR) surgery, we attempted pattern classification using an artificial neural network (ANN) of a surface electromyogram (s-EMG) extracted from an innervated muscle. The result shows that classification of only five motions was possible using an s-EMG extracted from four dry electrodes. However, seven motion classifications were possible using eight wet-gel electrodes. The transhumeral amputee who had TMR surgery could thus successfully perform pick-and-place tasks using the neuroprosthesis. GRAPHICAL ABSTRACT: